IBM DS8900F Architecture and Implementation - Dufrasne, Bertrand; Andorko, Gabor; Brunson, Sherri; Eriksson, Tony; Helmbrecht, Detlef; Kimmel, Peter; Martinez, Lisa; Shah, Kavita; Thierbach, Sandro (IBM Redbooks, 2020)
This IBM® Redbooks® publication describes the concepts, architecture, and implementation of the IBM DS8900F family. This book provides reference information to assist readers who need to plan for, install, and configure the DS8900F systems. This edition applies to DS8900F systems running microcode Release 9.0 (Bundle 89.0 / Licensed Machine Code (LMC) 7.9.0.xxx). The DS8900F family offers two new classes: IBM DS8910F: Flexibility Class all-flash: The Flexibility Class is designed to reduce complexity while addressing various workloads at the lowest DS8900F family entry cost. IBM DS8950F: Agility Class all-flash: The Agility Class is designed to consolidate all your mission-critical workloads for IBM Z®, IBM LinuxONE, IBM Power Systems, and distributed environments under a single all-flash storage solution. The DS8900F architecture relies on powerful IBM POWER9"!processor-based servers that manage the cache to streamline disk input/output (I/O), which maximizes performance and throughput. These capabilities are further enhanced by High-Performance Flash Enclosures (HPFE) Gen2. Like its predecessors, the DS8900F supports advanced disaster recovery (DR) solutions, business continuity solutions, and thin provisioning. The IBM DS8910F Rack-Mounted model 993 is described in a separate publication, IIBM DS8910F Model 993 Rack-Mounted Storage System, REDP-5566